Penguatan Peran Masyarakat Sadar Wisata Melalui Pencegahan Stunting dan Moderasi Beragama di Hutatoruan I - Yulia kurnia sari Sitepu; Liyus Waruwu (CANANG: Jurnal Pengabdian Masyarakat, 2025)
This community service aims to increase the awareness of residents of Hutatoruan I Village about their role in supporting the development of the tourism sector through stunting prevention and to promotion of religious moderation.  This study used a qualitative descriptive method with a community-based development approach, involving the participation of residents, community leaders, religious leaders, and village government in the planning, implementation, and evaluation of the activities. The results of the community service demonstrate an improvement in the community’s knowledge of tourism awareness, stunting prevention, and religious moderation, as evidenced by their increased engagement in tourism management and greater attention to environmental cleanliness. Interactive socialization activities, participatory dialogues, and the delivery of materials on tourism awareness, stunting, nutrition, and religious moderation enhanced community awareness, as well as the integration of tourism development, health, and socio-religious values, thereby positioning Hutatoruan I Village as a potential harmonious, healthy, and highly competitive tourist destination